Glyphosate-based herbicide exposure: effects on gill microbiota of rainbow trout (Oncorhynchus mykiss) and the aquatic bacterial ecosystem. Issue 8 (24th June 2022) - Bellec, Laure; Le Du-Carré, Jessy; Almeras, Fabrice; Durand, Lucile; Cambon-Bonavita, Marie-Anne; Danion, Morgane; Morin, Thierry
Abstract: The herbicide glyphosate has been widely used in the past 40 years, under the assumption that side effects were minimal. In recent years, its impact on microbial compositions and potential indirect effects on plant, animal and human health have been strongly suspected. Glyphosate and co-formulates have been detected in various water sources, but our understanding of their potential effects on aquatic animals is still in its infancy compared with mammals. In this study, we investigated the effect of chronic exposure to an environmentally relevant concentration of glyphosate on bacterial communities of rainbow trout ( Oncorhynchus mykiss ). Gills, gut contents and gut epithelia were then analyzed by metabarcoding targeting the 16S rRNA gene. Our results revealed that rainbow trout has its own bacterial communities that differ from their surrounding habitats and possess microbiomes specific to these three compartments. The glyphosate-based herbicide treatment significantly affected the gill microbiome, with a decrease in diversity. Glyphosate treatments disrupted microbial taxonomic composition and some bacteria seem to be sensitive to this environmental pollutant. Lastly, co-occurrence networks showed that microbial interactions in gills tended to decrease with chemical exposure. These results demonstrate that glyphosate could affect microbiota associated with aquaculture fish. Abstract : This study evalutes the impact of a low chronical exposition of glyphosate on gill and gut microbiomes of rainbow trout.